Where bacteria and eukaryotes meet - Chai, Liraz; Shank, Elizabeth A.; Zaburdaev, Vasily (Journal of Bacteriology, 2024)
The international workshop “Interdisciplinary life of microbes: from single cells to multicellular aggregates,” following a virtual preassembly in November 2021, was held in person in Dresden, from 9 to 13 November 2022. It attracted not only prominent experts in biofilm research but also researchers from broadly neighboring disciplines, such as medicine, chemistry, and theoretical and experimental biophysics, both eukaryotic and prokaryotic. Focused brainstorming sessions were the special feature of the event and are at the heart of this commentary.
CRIS-Team Scopus Importer:2024-03-01
Keywords: extracellular matrix; KEYWORDS biofilms; mechanosensing; multicellularity; tissues; workshop